PENGARUH PUPUK KANDANG TERHADAP P-TERSEDIA PUPUK FOSFAT ALAM YANG DIINOKULASI BAKTERI PELARUT FOSFAT - Sudadi Sudadi (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2010)
Title : The Effect of Manure on Available-P of Phosphate Rock Fertilizer Inoculated with P-solubilizer Bacteria. Experiment conducted at Soil Biology Laboratory, Faculty of Agriculture UNS Surakarta. This experiment aimed to study the effect of manure on solubilising capacity of P-solubilizer bacteria on phosphate rock fertilizer. The experiment arranged in completely randomized design with two factors i.e. dosages of manure added and inoculums rates of P-solubilizer bacteria (PSB) (Bacillus megatherium var phosphaticum). The manure added were 0 g (K0), 250 g (K1), and 500 g (K2) per 5 kg phosphate rock fertilizer. While the PSB inoculums rates were 0 cell/g (B0), 5.105 cell/g (B1) and 10.105 cell/g of phosphate rock fertilizer. The variables analysed at 2, 4 and 6 weeks after incubation for available-P, pH, organic matter content and total PSB. Data analysed with F test and DMRT at 95 % level of significant. The result indicated that available-P of phosphate rock fertilizer was significantly affected by PSB inoculation rates, doses of manure and incubation time. Available-P increase coincided with increasing of PSB inoculums and manure rates as well as incubation time. Treatment combination of PSB at 10.105 cell/g and manure of 500 g/ 5 kg increase available-P up to 80.59 ppm (151.5 % of the control treatment) at the end incubation time. Keywords: Manure, Phosphate Rock Fertilizer, P-solubilizer Bacteria